Infusion of Creative Thinking Skills into Arabic Curriculum in Nigerian higher Institutions to enhance graduates’ Employment - Adeniyi, Shittu Morufudeen; Yusuf, Muhammed (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This Paper discussed the inclusion of creative thinking skills into the existing Arabic curriculum in Nigeria’s tertiary institutions to provide more job opportunities for Arabic graduates. The study used a total population of 1350 students selected across universities and colleges of education in Yorubaland, Nigeria. Out of this population, 303 samples were finally drawn for the study. The research question of the study is to what extent Arabic curriculum content predicts employability skills of the graduates? The research hypotheses are: Arabic Curriculum content predicts creative thinking skills of the graduates in Nigeria, and b) R0: Arabic curriculum content does not predict creative thinking skills of the graduates in Nigeria. The Principal component analysis, Simple Regression Analysis, and other statistical tools were used for data analysis. The findings of the study show that there is a significant relationship between creative thinking skills and content of Arabic language. Moreover, Arabic curriculum content predicts creative thinking skills of Arabic graduates. Significantly, the study contributes to the field of Arabic studies by introducing creative thinking skills as an added advantage to Arabic graduates. This study proposed employability package that comprises of creative thinking skills to increase Arabic graduates’ chances to get lucrative jobs. The government must also ensure adhering the usage of the creative thinking skills in Arabic curriculum across all universities and colleges of educations offering Arabic language. Lastly, students of Arabic language must face challenges ahead of them and make themselves marketable to prospective employers just like their counterparts in other fields of study.